Resistance to wheat stripe mosaic virus (WhSMV): response of contrasting wheat genotypes under infection in the field - Pereira F.S.* (2024)
© The Author(s), under exclusive license to Sociedade Brasileira de Fitopatologia 2023.Southern South America's main winter cash crop is wheat (Triticum aestivum L.). Wheat stripe mosaic virus (WhSMV, Benyviridae) cause soil-borne wheat mosaic disease (SBWMD) in Brazil, and is a recurrent threat that reduces grain yields in southern Brazil and Paraguay. For many years, field tests in Brazil have used visual evaluations of symptom severity to measure how wheat cultivars respond to this virus and even the genetic inheritance of resistance. The WhSMV genome sequencing process made it feasible to detect and quantify the virus just recently. This research aims to determine a correlation between the severity of symptoms and virus titer by measuring WhSMV in wheat cultivars by RT-qPCR using the absolute quantification technique. In a field with a history of the SBWMD, seven cultivars were assessed in order to confirm the symptom manifestation (severity scale), plant height, and grain yield. Primers were designed and developed the RT-qPCR technique to relate visual notes of symptoms (the disease index) with the virus titer. The virus was found in all genotypes and variations between the visual severity and viral titer in the plants were detected, indicating that viral replication is not the only factor affecting the intensity of symptoms in this pathosystem.